Analisis Usia dan Lama Penggunaan dengan Frekuensi Keluhan Penggunaan Kontrasepsi Vasektomi di Desa Giripurwo Kulonprogo Daerah Istimewa Yogyakarta - Wiwin Hindriyawati; Silvy Wafda Nur Amelia (Jurnal Medika Cendikia, 2018)
Vasectomy among people is still poorly understood, and many myths are circulating about the consequent impacts / complaints that arise after the use of vasectomy. Vasectomy one of the permanent contraceptive methods for men performed with surgery / small surgery, has a very high effectiveness. However, the use of contraception for men is very small compared to other contraceptives in Indonesia. Efforts to reduce the birth rate, not just the responsibility of women, the responsibility of husband and wife, the participation of men in this case berKB husband, then the success of the KB program becomes the determinant. Vasectomy in Kulonprogo Regency although its development is encouraging but has not reached the target. 2013 has exceeded the target and in 2014 this optimist can reach the target. Galur districts there is no male contraception participants for vasectomy and the highest vasectomy achievement is Girimulyo districts. Still low contraception men, because of the existence of the understanding of male vasectomy will be castrated, but not like that. Vasectomy can still be connected again. Objective, to knowing Age Analysis And Old Usage With Frequency Of Complaint Using Vasectomy Contraception. Methods with Analytical survey method, sampling technique in total sampling that is as much as 59 Respondents. Intrument used using likert scale. Analyzed using multivariate. Results show up characteristic of most respondents, > 40 years old (79.7%), primary education (62.7%), most farmers (69.5%), number of children owned ≤2 (66.1%) , duration of use ≤ 5 years (66,1%). Frequency of complaints of vasectomy use at the frequency of 50.8% of minor complaints. The old relationship of use with the frequency of complaints p 0.309. Crosstab result most ≤ 5 years with mild complaint frequency 56%. The relationship between age and frequency of complaints p value: 0.696. Results crosstab age> 40 years most with light frequency 80%. Age analysis, duration with frequency of complaint use of vasectomy contraception F arithmetic (1,109). Conclusion, no relationship between age and duration of use with frequency of vasectomy complaints